Implementation and Evaluation of an Intervention for Children in Afghanistan at Risk for Substance Use or Actively Using Psychoactive Substances. (5th July 2017) - Momand, Abdul Subor; Mattfeld, Elizabeth; Morales, Brian; Ul Haq, Manzoor; Browne, Thom; O'Grady, Kevin E.; Jones, Hendrée E.
Abstract : The present study examined the impact of a novel intervention for children at risk for substance use or actively using substances that was provided to 783 children between 4 and 18 years of age in Afghanistan. They received the Child Intervention for Living Drug-free (CHILD) protocol while in outpatient or residential treatment. CHILD included age-appropriate literacy and numeracy, drug education, basic living safety, and communication and trauma coping skills. A battery of measures examined multiple child health domains at treatment's start and end and 12 weeks later. For younger children, there were no significant Gender or Gender X Time effects (all p 's > .16 and .35, resp.). The time main effect was significant for all outcomes (all p 's < .00192, the prespecified per-comparison error rate). Post hoc testing showed significant improvements from residential treatment entry to completion for all scales. For older children, a time main effect was significant for (all p 's < .00192, the prespecified per-comparison error rate) all but one outcome. Community follow-up means were significantly lower than residential treatment entry means. CHILD had a positive impact on children, and treatment impact endured from posttreatment to follow-up assessment.